Effects of lateral nitrate flux and instream processes on dissolved inorganic nitrogen export in a forested catchment: A model sensitivity analysis. Issue 4 (20th April 2015) - Lin, Laurence; Webster, Jackson R.; Hwang, Taehee; Band, Lawrence E.
Abstract The importance of terrestrial and aquatic ecosystems in controlling nitrogen dynamics in streams is a key interest of ecologists studying dissolved inorganic nitrogen (DIN) export from watersheds. In this study, we coupled a stream model with a terrestrial ecohydrological model and conducted a global sensitivity analysis to evaluate the relative importance of both ecosystems to nitrogen export. We constructed two scenarios ("normal" and high nitrate loads) to explore conditions under which terrestrial (lateral nitrate flux) or aquatic ecosystems (instream nutrient processes) may be more important in controlling DIN export. In a forest catchment, although the forest ecosystem controls the nitrogen load to streams, sensitivity results suggested that most nitrogen output from the terrestrial ecosystem was taken up by instream microbial immobilization associated with benthic detritus and retained in detritus. Later the immobilized nitrogen was remineralized as DIN. Therefore, the intra‐annual pattern of DIN concentration in the stream was low in fall and became high in spring. Not only was instream microbial immobilization saturated with the high nitrogen load scenario, but also the net effect of immobilization and mineralization on DIN export was minimized because nitrogen cycling between organic and inorganic forms was accelerated. Overall, our linked terrestrial‐aquatic model simulations demonstrated that stream process could significantly affect the amount and timing of watershed nitrogen export when nitrogen export from the terrestrial system is low. However, when nitrogen export from the terrestrial system is high, the effect of stream processes is minimal.